Immunochromatographic food control tools: New developments and practical prospects - A. V. Zherdev; E. A. Zvereva; N. A. Taranova; I. V. Safenkova; N. L. Vostrikova; B. B. Dzantiev (Теория и практика переработки мяса, 2025)
In the modern food production technologies, the tools and means of simple and rapid testing raw materials, intermediate products and the final ready-to-consume food products are in high demand. This monitoring allows determining the content of toxic and pathogenic contaminants and confirms the compliance of the objects being tested with the established regulatory requirements. Mobile tests tools and means (so called test systems) provide the opportunity of wide range monitoring without involving the specialized laboratories and highly qualified specialists. Thus, test systems for detection of toxic and pathogenic contaminants serve as the useful addition to confirming instrumental analytical methods. An actively developing approach for this field testing is the using of immunochromatographic test strips, in which strips all the necessary reagents are applied to the membrane components of the analytical system. Contact of the test strip with the sample being tested, initiates all further interactions and generates the recordable or visually assessable optical signal. The market of test systems based on immunochromatographic analysis is constantly growing, thus offering the permanently widening choice of solutions. However, in recent years there has been a real boom of new developments in immunochromatography field, thus offering various options for highly sensitive and information capacitive analytical systems. This study systematizes these developments and provides their comparative assessment in terms of prospects for their technological implementation and practical application in the coming years. The opportunities of designing the antibodies and alternative receptor molecules for controlling the affinity and the selectivity of recognition of the compounds being monitored are considered. The advantages and limitations of the new nanodispersed markers and non-optical methods for their registration in immunochromatography are discussed. The methods for quantitative assessment of the contaminants content via immunochromatography are characterized. The developed design options of the test systems for multiplex control — simultaneous detection of several compounds — are presented. Examples of integration of immunochromatographic tests with the systems of automatic registration, processing, transfer, storage and analysis of results of numerous tests are represented.